Efficiency Analysis of Concurrently Driven Power Amplifiers - Tian Qi; Songbai He; Biao Hu; Chang Liu; Xuekun Du; Yulong Zhao; Mohamed Helaoui; Wenhua Chen; Fadhel M. Ghannouchi (IEEE Access, 2020)
In this work, the properties of a two-tone signal driven concurrent power amplifier (CPA) are analyzed extensively. Firstly, the characteristics of two-tone signals are discussed to explain the nonlinearity and efficiency of two-tone signal driven CPA. Secondly, a method of how to solve the efficiency of a two-tone signal driven CPA is proposed in this paper with a detailed calculation procedure and complete theory. Finally, a general empirical expression to calculate the drain efficiency (DE) of CPA versus the frequency ratio and the amplitude ratio of the two carriers is proposed. Simulation results and experimental verifications are given to validate the proposed analytical formulation to predict the efficiency of CPAs when driven with balanced or imbalanced two-tone signals.